2012
DOI: 10.1098/rspb.2012.0181
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential for egg chemoattractants to mediate sexual selection in a broadcast spawning marine invertebrate

Abstract: In numerous species, egg chemoattractants play a critical role in guiding sperm towards unfertilized eggs (sperm chemotaxis). Until now, the known functions of sperm chemotaxis include increasing the effective target size of eggs, thereby promoting sperm–egg encounters, and facilitating species recognition. Here, we report that in the broadcast spawning mussel, Mytilus galloprovincialis , egg chemoattractants may play an unforeseen role in sexual selection by enabling sperm to effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(126 citation statements)
references
References 33 publications
6
117
3
Order By: Relevance
“…egg choice) revealed significant male-by-female interaction effects (table 2). Thus, consistent with previous findings for this species [22], the strength of chemically moderated gamete preferences was contingent on the specific identities of eggs and sperm present in each trial. Similarly, in the no-choice assays, fertilization rates, larval survival and the two composite measures of sperm motility (PC1 and PC2) were influenced by the interacting effects of male and female identities (table 2).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…egg choice) revealed significant male-by-female interaction effects (table 2). Thus, consistent with previous findings for this species [22], the strength of chemically moderated gamete preferences was contingent on the specific identities of eggs and sperm present in each trial. Similarly, in the no-choice assays, fertilization rates, larval survival and the two composite measures of sperm motility (PC1 and PC2) were influenced by the interacting effects of male and female identities (table 2).…”
Section: Resultssupporting
confidence: 89%
“…This study adds two key findings to these previous analyses. First, we show that there are measurable fitness benefits associated with these chemically moderated gamete preferences; sperm preferentially swim towards eggs that not only deliver higher fertilization rewards (this study and [22]) but also those that yield higher post-zygotic survival rates. In other contexts, previous studies have reported significant male-by-female interactions at fertilization [33,34], but the question of whether 'compatible' combinations of sperm and eggs yield high post-zygotic survival has received less attention, and some studies investigating this topic in other contexts have reported no significant association between fertilization and offspring viability [23 -25].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, disentangling the separate effects of varying quality of sperm and differing ovarian fluids on fertilization success and offspring quality under sperm competition is challenging. Some authors have demonstrated positive effects of ovarian fluid on sperm velocity (Gasparini and Pilastro, 2011;Evans et al, 2012;Oliver and Evans, 2014;Alonzo et al, 2016;Rosengrave et al, 2016), while Lumley et al (2016) revealed no effect of ovarian fluid on relative offspring fitness. Moreover, the only published intraspecific study exchanging ovarian fluid between eggs from different females documented no overall effect of ovarian fluid on paternity success under sperm competition and no evidence for male-female interactions (Evans et al, 2013).…”
Section: Introductionmentioning
confidence: 99%